2015
DOI: 10.1080/10408398.2015.1087964
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic acid and its derivatives as naturally occurring compounds in foods and as additives: Uses, exposure, and controversy

Abstract: Benzoic acid is an aromatic carboxylic acid naturally present in plant and animal tissues, which can also be produced by microorganisms. Benzoic acid and a wide range of derivatives and related benzenic compounds, such as salts, alkyl esters, parabens, benzyl alcohol, benzaldehyde, and benzoyl peroxide, are commonly used as antibacterial and antifungal preservatives and as flavoring agents in food, cosmetic, hygiene, and pharmaceutical products. As a result of their widespread occurrence, production, and uses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(96 citation statements)
references
References 106 publications
1
95
0
Order By: Relevance
“…It can be produced by the plant as protection against fungal attacks. Benzoic acid and its derivatives have been employed in the food industry as antifungal and antibacterial food additives (Olmo, Calzada, & Nunez, ). Based on all the available data, we found that Thymus vulgaris and Thymbra spicata provided a relatively high amount of rosmarinic acid and benzoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…It can be produced by the plant as protection against fungal attacks. Benzoic acid and its derivatives have been employed in the food industry as antifungal and antibacterial food additives (Olmo, Calzada, & Nunez, ). Based on all the available data, we found that Thymus vulgaris and Thymbra spicata provided a relatively high amount of rosmarinic acid and benzoic acid.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to dietary factors, processed or fermented foods contain preservatives, including sorbic and benzoic acid. Sorbic acid is metabolized into t,t-muconic acid [39,40], while benzoic acid, which is contained in a variety of supplements such as soft drinks, dairy products, fruits, and spices, can be metabolized into hippuric acid and act as a confounder [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The data were consistent with previously published data [16,47] ( Supplementary Materials Figures S1-S3). The structure of compound 2, octadecyl benzoate (Figure 1), was elucidated with the help of IR, EI, NMR spectroscopy (including 2D NMR techniques), and by comparison with the literature [48]. It was obtained as colorless amorphous powder.…”
Section: Resultsmentioning
confidence: 99%